Crystal structures of silver (I) complexes with phenylthiourea and triphenylphosphine - Sofia Mekarat (Prince of Songkla University Faculty of Science (Physical Chemistry), 2013)
Thesis (M.Sc., Physical Chemistry)--Prince of Songkla University, 2010